Developing and Improving the Production Technology of Canned Cold Smoked Rainbow Trout Fillet - Aghababyan, A. M. (ՀԱԱՀ հիմնադրամ)
Fish and fish products are foods of high nutritional value. The current research aimed at improving the technology of manufacturing canned products from cold-smoked rainbow trout fillets has a certain scientific-practical significance. Physicochemical indicators of the mentioned product were studied in the experimental and control samples. It has been revealed that energy value of the product is higher in the experimental sample than in control one, due to the content of proteins and fats. HACCP system research has indicated that safety and biological indicators of the finished product meet the accepted standards. Therefore, the product is safe and can be offered to consumers.
Keywords: Food Science and Technology